National Ballad Creation Education Under Artificial Intelligence and Big Data - Liu, Xia; Han, Xiao; Lin, Xiao; Yang, Jong Hoon (Frontiers in Psychology, 2022)
The efficiency of manual ballad creation is low, and the status quo of music creation education still needs to be improved. Therefore, how to upgrade the creative level of students is studied to improve the creative ability of China’s unique ballad culture. The concept of music theory in the process of music creation is explained, and the application of big data in the NetEase cloud music platform is excavated. Besides, the optical music organization (OMR) method based on artificial intelligence (AI) is proposed using a learning method of style imitation. This method is applied to students’ ballad creation education and tested in the school creation curriculum. It is found that the novelty of the ballads created by the system is slightly better than the existing ballads by comparing the ballads created by the machine with those used as imitation templates. In addition, the students’ learning interests and creative achievement are compared through the comparative experiment. The results show that students’ interest in learning has been significantly improved, and their creative performance in oral language has also been enhanced compared with the control class. As a result, this system is considered to be able to be applied in students’ ballad creation courses and provide some basis for AI creation in related fields.